Web and Big Data 8th International Joint Conference, APWeb-WAIM 2024, Jinhua, China, August 30 - September 1, 2024, Proceedings, Part V - Zhang, Wenjie; Tung, Anthony; Zheng, Zhonglong; Yang, Zhengyi; Wang, Xiaoyang; Guo, Hongjie; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
The five-volume set LNCS 14961, 14962, 14963, 14964 and 14965 constitutes the refereed proceedings of the 8th International Joint Conference on Web and Big Data, APWeb-WAIM 2024, held in Jinhua, China, during August 30-September 1, 2024. The 171 full papers presented in these proceedings were carefully reviewed and selected from 558 submissions. The papers are organized in the following topical sections: Part I: Natural language processing, Generative AI and LLM, Computer Vision and Recommender System. Part II: Recommender System, Knowledge Graph and Spatial and Temporal Data. Part III: Spatial and Temporal Data, Graph Neural Network, Graph Mining and Database System and Query Optimization. Part IV: Database System and Query Optimization, Federated and Privacy-Preserving Learning, Network, Blockchain and Edge computing, Anomaly Detection and Security Part V: Anomaly Detection and Security, Information Retrieval, Machine Learning, Demonstration Paper and Industry Paper.
-- Anomaly Detection and Security. -- TWLog: Task Workflow-based Log Anomaly Detection. -- TS-AUBD: A Novel Two-Stage Method for Abnormal User Behavior Detection. -- Multi-Label Out-of-Distribution Detection with Spectral Normalized Joint Energy. -- Noisy Label Learning Based on Weighted Neighborhood Consistency. -- Information Retrieval. -- A New Learning-to-Rank Framework for Keyphrase Extraction using Multi-Scale Ratings and Feature Fusion. -- MIIGraph: Multi-Granularity InformationIntegration Graph for Document-Level Event Extraction. -- Multi-Granularity Neural Networks for Document-Level Relation Extraction. -- Improving Zero-Shot Information Retrieval with Mutual Validation of Generative and Pseudo- Relevance Feedback. -- Entity Semantic feature Fusion Network for Remote Sensing Image-Text Retrieval. -- Semantic Preservation and Hash Fusion Network for Unsupervised Cross-modal Retrieval. -- Machine Learning. -- Using High-Quality Feature for Weakly-Supervised Camouflaged Object Detection. -- ECHO: Adaptive Correction for Subgraph-wise Sampling with Lightweight Hyperparameter Search. -- A Parallel and Distributed Data Management Approach for MEC Using the Improved Parameterized Deep Q-Network. -- Clustering based Collaborative Learning Grouping for Knowledge Building. -- Unsupervised Feature Selection via Fuzzy K-Means and Sparse Projection. -- Open World Semi-Supervised Learning Based on Multi-Scale Enhanced Feature. -- ACD: Attention Driven Cognitive Diagnosis for New Learners Joining ITS. -- Data Augmentation for Knowledge Tracing based on Variational AutoEncoder and Efficient Network Reusing. -- An Epidemic Trend Prediction Model with Multi-Source Auxiliary Data. -- Lead-Aware Hierarchical Transformer and Convolution Fusion Network for ECG Classification. -- Reinforcement Learning From Clip. -- Self supervised contrastive learning combining equivariance and invariance. -- Demonstration Paper. -- FedPPQs: Optimizing Property Path Queries Evaluation over Federated RDF Systems. -- MPCPM: Multi-level Prevalent Co-location Pattern Miner. -- FGAQ: Accelerating Graph Analytical Queries Using FPGA. -- A Progressive Question Answering Framework Adaptable to Multiple Knowledge Sources. -- RocolSys: An Automatic Row-column Data Storage System For HTAP. -- MIPC-SHOPs: An Online System for Mining the Influence of Industrial Pollution on Cancer based on the Spatial High-influence Ordered-pair Patterns. -- A Perception System for DNS Root Service Status Based on Active and Passive Monitoring. -- Dynamic Route Planning System Integrated with Traffic Flow Sensing. -- NLITS: A Natural Language Interface for Time Series Databases. -- FOICP-Miner: An Interactive Spatial Pattern Recommendation System Based on Fuzzy-Ontology. -- SPCCP-Miner: Towards the Discovery of Congested Junctions. -- Crowd-OBIGAA Crowdsourced Approach for Oracle Bone Inscriptions Glyph Annotation. -- NexusDB: A Large-Scale Distributed Time-Series Database for Industrial Scenarios. -- Industry Paper. -- LMStor: Storage acceleration design for large models. -- Enhancing Emergency Communications via UAV-Assisted Home-Independent Broadband Mobile Networks. -- FPTSF: A Failure Prediction of hard disks based on Time Series Features towards low quality dataset. -- PMEMgreSQL: Embracing PostgreSQL with Persistent Memory. -- The Development of a TLA+ Verified Correctness Raft Consensus Protocol. -- Robust Multi-vehicle Routing with Communication Enhanced Multi-agent Reinforcement Learning for Last-mile Logistics. -- A Dual-tower Model for Station-level Electric Vehicle Charging Demand Prediction. -- BPGNN-SBR: Behavior Progressive Graph Neural Networks for Session-Based Recommendation. -- Exploring Simple Architecture of Just-in-Time Compilation in Databases.
Keywords: Data structures (Computer science).; Information theory; Application software; Image processing -- Digital techniques; Computer vision; Data mining; Big data; Data Structures and Information Theory; Computer and Information Systems Applications; Computer Imaging, Vision, Pattern Recognition and Graphics; Data Mining and Knowledge Discovery; Big Data